PENYISIPAN GEN FITASE PADA TANAMAN TEBU cv. PA 175 MELALUI Agrobacterium tumefaciens GV 2260 (pBinPI-IIEC) - Susiyanti .; Gustav Adolf Wattimena; Memen Surahman; Agus Purwito; Dwi Andreas Santosa (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACT Sugarcane (Saccharum officinarum L.) is one of importance crop grown in marginal in Indonesia. Phosphorus (P) is critical to the growth and development of plant in the marginal land. P is stored in plant as phytic acid (myo-inositolhexakisphosphate). Phytic acid is hydrolyzed by the activity of phytases to yield inositol and free phosphate. Genetic transformation of sugarcane with phytases gene holds promise to provide enough P during period of rapid cell division and growth of plant. Plant transformation mediated by Agrobacterium tumefaciens, has become the most used method for the introduction foreign genes into plant cells and the sub sequens regeneration of transgenic plant. The selection and regeneration of embryogenic callus of transformed plant was done on MS medium containing kanamycin. The main objective of this study were: (1) To find the best kanamycin concentration for selectable marker; (2) Insert phytase gen into varieties of sugarcane (cv. PA 175) through Agrobacterium tumefaciens GV 2260 (pBinPI-IIEC); and (3) To analyze of intregated transgene into genom of sugarcane using PCR method. Result of the experiment showed: (1) kanamycin selectable marker lethal doses for transformed sugarcane calli: 100 mg l-1; (2) Efficiency transformation of putative transgenic line was cv. PA 175= 24 %; (3) The first culture of transformed calli become 24 (Triton cv.), 18 (PSJT 94-41 cv.), and 30 (PA 175 cv.) putative plants; the second sub cullture of putative eksplant regenerate become new plant: 380 (PA 175 cv.) plants. (4) Analyzed of integrated phytase gene was proven by appearance of 900 bp of PCR band (5) transgenic plants (cv. PA 175) with highest activities respectively: 45 %; with medium phytase activity: 27 %, and low phytase activity: 27 % from total of sample. Non transgenic plants, most of sample show low phytase activity respectively: 100 % , noneh show medium - hight activy of phytase. Key words: Sugarcane, transformation, phytase, Agrobacterium tumefaciens